The Maitrāyaṇī saṁhitā, its ritual and language - Dharmādhikārī, Trivikrama Nārāyaṇa (Adarsha Sanskrit Shodha Samstha, 2008)
Study of the Maitrāyaṇīsaṃhitā, a recension of Kṛṣṇayajurveda, major division of Yajurveda, Hindu canonical text